Exploration of health care providers' knowledge-based care and support given to family members and caregivers of people living with epilepsy - Ofhani Prudance Musekwa; Lufuno Makhado; Angelina Maphula (Frontiers in Psychology, 2024)
IntroductionIn South Africa, approximately half a million individuals live with epilepsy. This means that half a million families and caregivers are impacted by epilepsy, with a limited number of healthcare providers responsible for treating people living with the condition, as well as their families and caregivers.MethodsThis study explored the knowledge-based care and support healthcare providers give families and caregivers. Fifteen participants were purposefully selected from Limpopo and Mpumalanga provinces to participate in the study. Data were collected via an open-ended interview guide divided into two sections: Section A comprised sociodemographic questions, and Section B had questions on epilepsy care and support. Four of the participants were male, and 11 were female, seven were community health workers, five were nurse practitioners, and three were auxiliary nurses. Seven had a grade 12 qualification or lower, and only six had a degree. The data collected was analyzed using thematic analysis, coded by the researcher and co-coded by an independent expert. Two themes emerged from the raw data: epilepsy knowledge and epilepsy support and counselling. From these two themes, three subthemes were identified: psychosocial impact of epilepsy, epilepsy-related training, and counselling and support.ResultsThe study revealed a gap in professional capacity building and highlighted the need for intentional knowledge sharing and equipping of healthcare providers.DiscussionThe findings suggest that equipping community health workers, in particular, may be a better and more efficient way to increase the quality of life for families and caregivers and people living with epilepsy in South Africa.